Polyamide resin composition and polyamide molded article

The polyamide resin composition, featuring a specific combination of dicarboxylic acid and diamine units with copper-based stabilizers and optional glass fibers, addresses the issue of reduced tensile strength in high temperature environments, ensuring prolonged strength retention and fluidity.

JP7665012B2Active Publication Date: 2025-04-18MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023507147
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-18
Filing Date
2022-03-16
Publication Date
2025-04-18
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

The addition of copper-based heat-resistant stabilizers to polyamide resin compositions improves heat-aging resistance but reduces the original tensile strength, particularly in high temperature environments.

Method used

A polyamide resin composition containing a component unit derived from an aromatic or alicyclic dicarboxylic acid and a diamine, with a copper-based heat-resistant stabilizer content between 0.001 and 0.050 parts by mass per 100 parts by mass of polyamide resin, and optionally including glass fibers with a surface treatment agent or focusing agent.

Benefits of technology

The polyamide resin composition effectively suppresses the decrease in tensile strength due to the copper-based stabilizer, maintaining a prescribed tensile strength for a longer period in high temperature environments, and maintains fluidity when glass fibers are added.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665012000001
    Figure 0007665012000001
  • Figure 0007665012000002
    Figure 0007665012000002
  • Figure 0007665012000003
    Figure 0007665012000003
Patent Text Reader

Abstract

Provided is a polyamide resin composition that, at high temperatures, is capable of suppressing reductions in tensile strength due to the addition of a copper-based heat stabilizer, and is capable of maintaining a prescribed tensile strength over longer periods of time in a hot environment. The polyamide resin composition includes a polyamide resin and a copper-based heat stabilizer. The polyamide resin includes: a component unit (a) derived from dicarboxylic acid which is derived from an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid; and greater than or equal to 10 mol% and less than 50 mol% of a component unit (b2), which is derived from 1,3-bis(aminomethyl)cyclohexane, with respect to the total number of moles of a component unit (b) derived from diamine. The content of copper included in the copper-based stabilizer is 0.001 parts by mass to 0.050 parts by mass, inclusive, with respect to 100 total parts by mass of the polyamide resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide resin composition and a polyamide molded article. [Background technology]

[0002] Polyamide resin compositions have been widely used as materials for various parts for clothing, industrial materials, automobiles, electrical and electronic products, industrial applications, etc. because of their excellent moldability, mechanical properties, and chemical resistance.

[0003] Various additives are added to the polyamide resin compositions used for these applications in order to develop properties according to the respective applications. For example, it is known that a copper-based heat stabilizer is added to improve the heat aging resistance of the polyamide resin composition. For example, Patent Document 1 describes that the time until the tensile strength is reduced by half when heat-treated at 180°C can be extended to several hundred hours by adding a copper-based heat stabilizer.

[0004] Also, attempts have been made to change the physical properties of polyamide resins by changing the raw materials of the polyamide resins. For example, Patent Document 2 and Patent Document 3 describe polyamide resins using 1,3-bis(aminomethyl)cyclohexane as a diamine component used in the production of polyamides by polycondensing a diamine component and a dicarboxylic acid component. Patent Document 2 describes that the polyamide resin described in said document has high transparency, and Patent Document 3 describes that the polyamide resin described in said document has a high glass transition point and improved crystallization ability.

[0005] Incidentally, it is also known that a reinforcing material such as glass fiber is blended to increase the impact resistance and rigidity of a polyamide resin composition. The glass fiber may be treated with a sizing agent or a surface treatment agent for the purpose of increasing the dispersibility in the polyamide resin. For example, Patent Document 1 describes a glass fiber sizing agent having a weight average molecular weight of 10,000 to 60,000, which contains a copolymer compound obtained by copolymerizing 20 to 60 mass% of an unsaturated dicarboxylic acid or carboxylic anhydride, 20 to 75 mass% of methyl acrylate, and 5 to 20 mass% of methyl methacrylate, aminosilane, and a polyurethane resin. Patent Document 1 describes that the sizing agent can increase the mechanical strength (particularly tensile strength) of the polyamide resin to which the glass fiber is added. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 06-032979 [Patent Document 2] Japanese Patent Publication No. 49-55796 [Patent Document 3] JP 2017-75303 A [Patent Document 4] JP 2014-231452 A Summary of the Invention [Problem to be solved by the invention]

[0007] As described in Reference 1, it is known that the heat aging resistance of a polyamide resin composition can be improved by a copper-based heat stabilizer. However, according to the new findings of the present inventors, the addition of a copper-based heat stabilizer causes a problem that the original tensile strength of the polyamide resin composition is reduced. The problem of the reduction in tensile strength is particularly noticeable when a molded body of the polyamide resin composition is used in a high-temperature environment. In addition, in recent years, there has been an increasing demand for further improving the long-term heat resistance of polyamide resin compositions, and there is a demand for the development of a polyamide resin composition that can maintain a predetermined tensile strength for a longer period of time in a high-temperature environment.

[0008] In view of these circumstances, an object of the present invention is to provide a polyamide resin composition that can suppress the decrease in tensile strength at high temperatures caused by the addition of a copper-based heat stabilizer and can maintain a predetermined tensile strength for a long period of time in a high-temperature environment, and a polyamide molded article containing the polyamide resin composition. [Means for solving the problem]

[0009] [1] A polyamide resin, Contains copper-based heat stabilizer, The polyamide resin is A polyamide resin comprising a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine, The dicarboxylic acid-derived component unit (a) includes an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid-derived component unit, The diamine-derived component unit (b) is a component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms, the component unit (b1) being more than 50 mol % and not more than 90 mol % of the total number of moles of the component unit (b) derived from the diamine; a component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane in an amount of 10 mol % or more and less than 50 mol % based on the total number of moles of the component units (b) derived from the diamine; Including, The copper content in the copper-based stabilizer is 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin contained in the polyamide resin composition. Polyamide resin composition. [2] The polyamide resin composition according to [1], further comprising glass fibers containing a surface treatment agent having an acidic group or a sizing agent having an acidic group, in an amount of 1 part by mass or more and 300 parts by mass or less per 100 parts by mass of polyamide resin contained in the polyamide resin composition. [3] The polyamide resin composition according to [2], wherein the acidic group is a carboxy group, an acid anhydride group, or an ester group. [4] The polyamide resin composition according to any one of [1] to [3], wherein the polyamide resin contains component units (b2) derived from 1,3-bis(aminomethyl)cyclohexane in an amount of 15 mol % or more and less than 45 mol % based on the total number of moles of the component units (b) derived from the diamine. [5] The component unit (b1) derived from an alkylenediamine having 4 to 18 carbon atoms includes a component unit derived from a linear alkylenediamine or a branched alkylenediamine. The polyamide resin composition according to any one of [1] to [4]. [6] The linear or branched alkylenediamine is a diamine selected from the group consisting of 1,4-diaminobutane, 1,6-diaminohexane, 1,9-nonanediamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine and 2-methyl-1,8-octanediamine; [5] The polyamide resin composition according to the present invention. [7] The aromatic dicarboxylic acid or alicyclic dicarboxylic acid is terephthalic acid, naphthalenedicarboxylic acid or cyclohexanedicarboxylic acid; The polyamide resin composition according to any one of [1] to [6]. [8] The polyamide resin composition according to any one of [1] to [7], which is a resin composition for an on-vehicle member. [9] The polyamide resin composition according to any one of [1] to [8], Polyamide molding.

[10] An in-vehicle component, The polyamide molding according to [9]. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a polyamide resin composition that can suppress the decrease in tensile strength caused by the addition of a copper-based heat stabilizer and can maintain a predetermined tensile strength for a long period of time in a high-temperature environment, and a polyamide molded product containing the polyamide resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0012] In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0013] 1. First embodiment A first embodiment of the present disclosure relates to a polyamide resin composition.

[0014] The polyamide resin composition is a resin composition in which the main component of the resin components is a polyamide resin. The main component means that the proportion of the polyamide resin in the resin components is 50% by mass or more. The proportion of the polyamide resin in the resin components is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The upper limit of the proportion of the polyamide resin in the resin components is not particularly limited, but can be 100% by mass or less, may be 90% by mass or less, or may be 80% by mass or less.

[0015] The proportion of the polyamide resin contained in the polyamide resin composition is preferably 20% by mass or more and 80% by mass based on the total mass of the polyamide resin composition.

[0016] 1-1.Polyamide resin The polyamide resin may be a polyamide resin containing a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine. In this case, in order to set the melting point (Tm) and glass transition temperature (Tg) of the polyamide resin within the above range, the component unit (a) derived from a dicarboxylic acid preferably contains a component unit derived from an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid, and the component unit (b) derived from a diamine preferably contains a component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms, which is more than 50 mol% and not more than 90 mol% of the total number of moles of the component unit (b) derived from the diamine, and a component unit (b1) derived from 1,3-bis(aminomethyl)cyclohexane, which is more than 10 mol% and not more than 50 mol% of the total number of moles of the component unit (b) derived from the diamine.

[0017] [Component unit (a) derived from dicarboxylic acid] When the polyamide resin contains a component unit derived from an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid as the component unit (a) derived from a dicarboxylic acid, the melting point (Tm) and crystallinity can be sufficiently increased.

[0018] Examples of aromatic dicarboxylic acids include terephthalic acid, naphthalenedicarboxylic acid, and their esters. Examples of alicyclic dicarboxylic acids include cyclohexanedicarboxylic acid and its esters. Among them, from the viewpoint of obtaining a polyamide resin having high crystallinity and high heat resistance, the component unit (a) derived from a dicarboxylic acid preferably includes a component unit derived from an aromatic dicarboxylic acid, and more preferably includes a component unit derived from terephthalic acid.

[0019] The content of the component unit derived from an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid (preferably a component unit derived from an aromatic dicarboxylic acid, more preferably a component unit derived from terephthalic acid) is not particularly limited, but is preferably 50 mol% or more and 100 mol% or less based on the total number of moles of the component unit (a) derived from a dicarboxylic acid. If the content of the component unit is 50 mol% or more, the crystallinity of the polyamide resin is easily increased. From the same viewpoint, the content of the component unit is more preferably 70 mol% or more and 100 mol% or less.

[0020] In this embodiment, the component unit (a) derived from a dicarboxylic acid preferably includes a component unit (a1) derived from terephthalic acid, naphthalenedicarboxylic acid, or cyclohexanedicarboxylic acid. These component units (a1) can enhance the crystallinity of polyamide, unlike, for example, isophthalic acid. The content of these component units (a1) is set to more than 20 mol% and not more than 100 mol% based on the total number of moles of the component units (a) derived from dicarboxylic acid, from the viewpoint of ensuring the crystallinity of the polyamide resin. From the viewpoint of further enhancing the crystallinity of the polyamide resin, the content of these component units (a1) is preferably 45 mol% or more and 100 mol% or less based on the total number of moles of the component units (a) derived from dicarboxylic acid, more preferably 50 mol% or more and 99 mol% or less, even more preferably 80 mol% or more and 99 mol% or less, and particularly preferably 90 mol% or more and 99 mol% or less.

[0021] The dicarboxylic acid-derived component unit (a) may contain aromatic carboxylic acid component units (a2) other than the above component unit (a1) or aliphatic dicarboxylic acid component units (a3) ​​having 4 to 20 carbon atoms, provided that the effects disclosed herein are not impaired. However, from the viewpoint of not impairing the crystallinity of the resin, the content of component units derived from isophthalic acid and component units derived from aliphatic dicarboxylic acids having 4 to 18 carbon atoms other than adipic acid is small, specifically, preferably 20 mol % or less, more preferably 10 mol % or less, based on the total number of moles of the dicarboxylic acid-derived component units (a).

[0022] Examples of aromatic dicarboxylic acid component units (a2) other than terephthalic acid include component units derived from isophthalic acid and 2-methylterephthalic acid. Among these, component units derived from isophthalic acid are preferred. From the viewpoint of ensuring the crystallinity of the polyamide resin, the content of these component units (a2) is preferably 1 mol% or more and 50 mol% or less, more preferably 1 mol% or more and 20 mol% or less, even more preferably 1 mol% or more and 10 mol% or less, and particularly preferably 1 mol% or more and 5 mol% or less, based on the total number of moles of component units (a) derived from dicarboxylic acid.

[0023] The component unit (a3) ​​derived from an aliphatic dicarboxylic acid is a component unit derived from an aliphatic dicarboxylic acid having an alkylene group with 4 to 20 carbon atoms, and is preferably a constituent unit derived from an aliphatic dicarboxylic acid having an alkylene group with 6 to 12 carbon atoms. Examples of the aliphatic dicarboxylic acid include malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, and suberic acid component units. Among these, adipic acid and sebacic acid are preferred. From the viewpoint of ensuring the crystallinity of the polyamide resin, the content of these component units (a3) ​​is preferably 0 mol% to 40 mol%, more preferably 0 mol% to 20 mol%, even more preferably 1 mol% to 10 mol%, and particularly preferably 1 mol% to 5 mol% based on the total moles of the component units (a) derived from dicarboxylic acids.

[0024] The semi-aromatic polyamide resin (A) may further contain a small amount of a tribasic or higher polybasic carboxylic acid unit such as trimellitic acid or pyromellitic acid in addition to the above-mentioned component units (a1), (a2), and (a-3). The content of such a polybasic carboxylic acid unit may be 0 mol% or more and 5 mol% or less based on the total number of moles of the component units (a) derived from dicarboxylic acids.

[0025] [Diamine-derived component unit (b)] When the polyamide resin contains, as the diamine-derived component unit (b), a component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane in addition to a component unit (b1) derived from an alkylene diamine having from 4 to 18 carbon atoms, the glass transition temperature (Tg) can be sufficiently increased.

[0026] That is, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane has a nonlinear structure, and therefore reduces the mobility of the molecular chain of the polyamide resin. Therefore, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane can increase the glass transition temperature (Tg) of the polyamide resin having the component unit (b2) compared to the polyamide resin not having the component unit (b2). In addition, it is believed that this allows the polyamide resin having the component unit (b2) to have high mechanical strength even in a high temperature and high humidity pure environment, and to maintain this high mechanical strength for a long period of time.

[0027] Furthermore, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane can appropriately lower the melting point (Tm) of a polyamide resin having the component unit (b2) as compared to a polyamide resin not having the component unit (b2), thereby providing the polyamide resin with high fluidity during injection molding and high moldability.

[0028] According to the findings of the present inventors, the copper-based heat stabilizer described below is more effective at increasing the stability of the polyamide resin composition at high temperatures (for example, 150°C or higher) than the organic heat stabilizer, and therefore can more effectively increase the heat aging resistance of the polyamide resin composition. However, the copper-based heat stabilizer itself is a foreign matter in the resin composition and is a compound containing a metal whose properties are significantly different from those of the resin, so it greatly reduces the crystallinity of the polyamide resin and tends to reduce the original tensile strength of the polyamide resin composition from the initial production stage. In addition, in a high-temperature environment where the fluidity of the resin is high, the copper-based heat stabilizer, which is a foreign matter, tends to move more freely in the composition, and the movement of the resin molecules is more likely to hinder the expansion / contraction and crystallization, so that the decrease in tensile strength is more likely to occur. In contrast, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane increases the glass transition temperature of the polyamide resin, thereby restricting the movement of the copper-based heat stabilizer in a high-temperature environment. This is believed to make it less likely that the copper-based heat stabilizer will inhibit the expansion / contraction of resin molecules and the crystallization from being hindered, thereby suppressing the decrease in tensile strength of the polyamide resin composition in a high-temperature environment.

[0029] In addition, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane has a cyclic structure, so that the molecular chain of the resin is unlikely to be cut even when placed in a high-temperature environment for a long time, and the long-term heat resistance of the polyamide resin itself is improved. Therefore, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane is thought to make it easier to maintain the tensile strength of a molded article of the polyamide resin composition for a long period of time even in a high-temperature environment.

[0030] In addition, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane bends the molecular chain of the polyamide resin, thereby suppressing the penetration of moisture into the inside of the polyamide resin composition. As a result, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane makes the polyamide resin less susceptible to hydrolysis. This is thought to suppress the decrease in mechanical strength (particularly tensile strength) of a molded article of the polyamide resin composition, particularly under high temperature and high humidity conditions.

[0031] In addition, the polyamide resin has high fluidity and mechanical strength during injection molding because it has crystallinity due to the component unit (b1) derived from an alkylenediamine having from 4 to 18 carbon atoms. Furthermore, the polyamide resin has high mechanical strength even in a high temperature range because of its high glass transition temperature (Tg), and is considered to be able to easily maintain this high mechanical strength.

[0032] The number of carbon atoms in the alkylenediamine having 4 to 18 carbon atoms, which is the raw material of the component unit (b1), is more preferably 4 to 10, from the viewpoint of preventing a decrease in the Tg of the resin.

[0033] The alkylenediamine having 4 to 18 carbon atoms may include a linear alkylenediamine or a branched alkylenediamine. From the viewpoint of enhancing the crystallinity of the resin, the alkylenediamine having 4 to 18 carbon atoms preferably includes a linear alkylenediamine. That is, the component unit derived from the alkylenediamine having 4 to 18 carbon atoms preferably includes a component unit derived from a linear alkylenediamine.

[0034] Examples of alkylenediamines having 4 to 18 carbon atoms include linear alkylenediamines including 1,4-diaminobutane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine, and branched alkylenediamines including 2-methyl-1,5-pentanediamine and 2-methyl-1,8-octanediamine. Among these, 1,4-diaminobutane, 1,6-diaminohexane, 1,9-nonanediamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine are preferred, and 1,6-diaminohexane and 1,10-decanediamine are preferred. These alkylenediamines may be one type or two or more types.

[0035] The content of the component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms is preferably more than 50 mol% and not more than 90 mol% based on the total number of moles of the component unit (b) derived from the diamine. When the content is more than 50 mol%, the crystallinity of the polyamide resin can be sufficiently increased, and the flowability and mechanical strength of the resin during injection molding can be further increased. When the content is not more than 90 mol%, the content of the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane can be increased. This increases the glass transition temperature (Tg) of the polyamide resin, increasing the mechanical strength in the high temperature range, and appropriately lowering the (Tm) of the polyamide resin, thereby improving the moldability.

[0036] On the other hand, the content of the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane is preferably 10 mol% or more and less than 50 mol% based on the total number of moles of the component unit (b) derived from the diamine. When the content is 10 mol% or less, the glass transition temperature (Tg) of the polyamide resin is increased, the mechanical strength in the high temperature range is increased, and the (Tm) of the polyamide resin is appropriately decreased, thereby improving the moldability. When the content is less than 50 mol%, the content of the component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms can be increased. This can sufficiently increase the crystallinity of the polyamide resin to further increase the mechanical strength of the molded product, and can also suppress the decrease in the fluidity of the polyamide resin itself due to the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane.

[0037] From the above viewpoints, the content of the component units (b1) derived from an alkylene diamine having from 4 to 18 carbon atoms is preferably more than 50 mol % and not more than 90 mol %, more preferably from 55 mol % to 85 mol %, and even more preferably from 60 mol % to 80 mol %, based on the total number of moles of the component units (b) derived from diamine.

[0038] From the above viewpoints, the content of the component units (b2) derived from 1,3-bis(aminomethyl)cyclohexane is preferably 10 mol % or more and less than 50 mol %, more preferably 15 mol % or more and less than 45 mol %, even more preferably 20 mol % or more and 40 mol % or less, still more preferably 20 mol % or more and 38 mol % or less, and particularly preferably 20 mol % or more and 33 mol % or less, relative to the total number of moles of the component units (b) derived from diamine.

[0039] The diamine-derived component unit (b) may further contain another diamine-derived component unit (b3) within the range not impairing the effects disclosed herein. Examples of the other diamine include aromatic diamines and alicyclic diamines. The content of the other diamine-derived component unit (b3) may be 50 mol % or less based on the total number of moles of the diamine-derived component unit (b).

[0040] In order to improve the thermal stability during compounding or molding and to further increase the mechanical strength, at least some of the molecular terminal groups of the polyamide resin may be blocked with a terminal blocking agent. When the molecular terminal is a carboxyl group, the terminal blocking agent is preferably a monoamine, and when the molecular terminal is an amino group, the terminal blocking agent is preferably a monocarboxylic acid.

[0041] Examples of monoamines include aliphatic monoamines including methylamine, ethylamine, propylamine, and butylamine, alicyclic monoamines including cyclohexylamine and dicyclohexylamine, and aromatic monoamines including aniline and toluidine. Examples of monocarboxylic acids include aliphatic monocarboxylic acids having 2 to 30 carbon atoms including acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, oleic acid, and linoleic acid, aromatic monocarboxylic acids including benzoic acid, toluic acid, naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid, and alicyclic monocarboxylic acids including cyclohexanecarboxylic acid. The aromatic monocarboxylic acid and the alicyclic monocarboxylic acid may have a substituent on the ring structure portion.

[0042] [Physical Properties] The polyamide resin can have a melting point (Tm) of 280°C or more and 330°C or less, as measured by a differential scanning calorimeter (DSC), and a glass transition temperature (Tg) of 135°C or more and 180°C or less, as measured by DSC.

[0043] When the melting point (Tm) of the polyamide resin is 280° C. or higher, the mechanical strength and heat resistance of the polyamide resin composition and molded article in the high temperature range are not easily impaired, and when it is 330° C. or lower, the molding temperature does not need to be excessively high, so that the molding processability of the polyamide resin composition is likely to be good. From the above viewpoint, the melting point (Tm) of the polyamide resin is more preferably 290° C. or higher and 330° C. or lower, and further preferably 300° C. or higher and 330° C. or lower.

[0044] When the glass transition temperature (Tg) of the polyamide resin is 135° C. or higher, the heat resistance of the polyamide resin composition and the molded article is not easily impaired, and at the same time, the mechanical strength at high temperatures can be increased. When the glass transition temperature (Tg) of the polyamide resin is 180° C. or lower, the moldability of the polyamide resin composition is likely to be good. From the above viewpoint, the glass transition temperature (Tg) of the polyamide resin is more preferably 140° C. or higher and 170° C. or lower.

[0045] When the glass transition temperature (Tg) of the polyamide resin is 135°C or higher and the difference between the melting point (Tm) and the glass transition temperature (Tg) of the polyamide resin is 170°C or lower, the polyamide resin composition can have high mechanical strength in the high temperature range and high heat resistance and curing property due to the suppression of decomposition of the copper-based heat stabilizer, and the decrease in fluidity during injection molding due to the addition of a sizing agent having an acidic group or glass fiber treated with a surface treatment agent can be suppressed. From the above viewpoint, it is more preferable that the glass transition temperature (Tg) is 140°C or higher and the difference between the melting point (Tm) and the glass transition temperature (Tg) of the polyamide resin is 120°C or higher and 170°C or lower, and it is even more preferable that the glass transition temperature (Tg) is 150°C or higher and the difference between the melting point (Tm) and the glass transition temperature (Tg) of the polyamide resin is 130°C or higher and 165°C or lower.

[0046] The heat of fusion (ΔH) of the crystalline polyamide resin is preferably 10 mJ / mg or more. When the heat of fusion (ΔH) of the crystalline polyamide resin is 10 mJ / mg or more, it has crystallinity, and therefore it is easy to improve the flowability and mechanical strength during injection molding. From the same viewpoint, the heat of fusion (ΔH) of the crystalline polyamide resin is more preferably 15 mJ / mg or more, and even more preferably 20 mJ / mg or more. The upper limit of the heat of fusion (ΔH) of the crystalline polyamide resin is not particularly limited, but it may be 90 mJ / mg from the viewpoint of not impairing the moldability.

[0047] The heat of fusion (ΔH), melting point (Tm) and glass transition temperature (Tg) of the polyamide resin can be measured using a differential scanning calorimeter (DSC220C, manufactured by Seiko Instruments Inc.).

[0048] Specifically, about 5 mg of polyamide resin is sealed in a measuring aluminum pan and heated from room temperature to 350°C at 10°C / min. In order to completely melt the resin, it is held at 360°C for 3 minutes and then cooled to 30°C at 10°C / min. After leaving it at 30°C for 5 minutes, it is heated a second time to 360°C at 10°C / min. The temperature (°C) of the endothermic peak in this second heating is the melting point (Tm) of the crystalline polyamide resin, and the transition point corresponding to the glass transition is the glass transition temperature (Tg). The heat of fusion (ΔH) is calculated from the area of ​​the endothermic peak of crystallization during the first heating process in accordance with JIS K7122.

[0049] The melting point (Tm), glass transition temperature (Tg) and heat of fusion (ΔH) of the crystalline polyamide resin can be adjusted by the structure of the component unit (a) derived from dicarboxylic acid, the content of the component unit (b2) derived from the diamine represented by formula (1), the content ratio of the component unit (b1) derived from an alkylenediamine having 4 to 18 carbon atoms to the component unit (b2) derived from the diamine represented by formula (1), and the number of carbon atoms of the alkylenediamine having 4 to 18 carbon atoms.

[0050] Furthermore, when increasing the heat of fusion (ΔH) of the crystalline polyamide resin, it is preferable to reduce the content or ratio of the component unit (b2) (the ratio of the component unit (b2) to the total number of moles of the component unit (b) derived from the diamine). On the other hand, when increasing the glass transition temperature (Tg) and decreasing the melting point (Tm) of the crystalline polyamide resin, it is preferable to increase the content or ratio of the component unit (b2) (the ratio of the component unit (b2) to the total number of moles of the component unit (b) derived from the diamine), for example.

[0051] The intrinsic viscosity [η] of the crystalline polyamide resin measured in 96.5% sulfuric acid at a temperature of 25° C. is preferably 0.6 dl / g or more and 1.5 dl / g or less. When the intrinsic viscosity [η] of the crystalline polyamide resin is 0.6 dl / g or more, the mechanical strength (toughness, etc.) of the molded body is easily increased, and when it is 1.5 dl / g or less, the fluidity during molding of the resin composition is not easily impaired. From the same viewpoint, the intrinsic viscosity [η] of the crystalline polyamide resin is more preferably 0.8 dl / g or more and 1.2 dl / g or less. The intrinsic viscosity [η] can be adjusted by the amount of terminal blocking of the crystalline polyamide resin, etc.

[0052] The intrinsic viscosity of the crystalline polyamide resin can be measured in accordance with JIS K6810-1977. Specifically, 0.5 g of crystalline polyamide resin is dissolved in 50 ml of 96.5% sulfuric acid solution to prepare a sample solution. The flow time of this sample solution is measured using an Ubbelohde viscometer under conditions of 25±0.05°C, and the obtained value is applied to the following formula to calculate the flow time. [η]=ηSP / [C(1+0.205ηSP)]

[0053] In the above formula, each algebra or variable represents the following: [η]: Intrinsic viscosity (dl / g) ηSP: Specific viscosity C: Sample concentration (g / dl)

[0054] ηSP is calculated by the following formula: ηSP=(t-t0) / t0 t: Time required for sample solution to flow (seconds) t0: Number of seconds that blank sulfuric acid flows (seconds)

[0055] [Manufacturing method] The polyamide resin can be produced, for example, by polycondensing the above-mentioned dicarboxylic acid and the above-mentioned diamine in a homogeneous solution. Specifically, the dicarboxylic acid and the diamine are heated in the presence of a catalyst as described in WO 03 / 085029 to obtain a low-order condensate, and then the melt of the low-order condensate is subjected to shear stress to polycondense the low-order condensate.

[0056] From the viewpoint of adjusting the intrinsic viscosity of the polyamide resin, the above-mentioned terminal blocking agent may be added to the reaction system. The intrinsic viscosity [η] (or molecular weight) of the polyamide resin can be adjusted by the amount of terminal blocking agent added.

[0057] The terminal blocking agent is added to the reaction system of the dicarboxylic acid and the diamine, and the amount added is preferably 0.07 mol or less, and more preferably 0.05 mol or less, per 1 mol of the total amount of the dicarboxylic acid.

[0058] 1-2.Heat stabilizer The copper-based heat stabilizer can improve the fluidity of the polyamide resin composition during molding by being contained together with the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane. This improvement in fluidity is believed to be due to the fact that the component unit derived from 1,3-bis(aminomethyl)cyclohexane suppresses entanglement of molecular chains, and the effect of reducing viscosity by adding the copper-based heat stabilizer is more pronounced. In addition, the copper-based heat stabilizer improves the heat aging resistance of the resin composition.

[0059] The copper-based heat resistance stabilizer preferably contains (i) a salt of a halogen and a metal element of Group 1 or 2 of the Periodic Table, i.e., a halogen metal salt, and (ii) a copper compound. Furthermore, it preferably further contains (iii) a metal salt of a higher fatty acid, as necessary.

[0060] (i) Examples of halogen metal salts include potassium iodide, potassium bromide, potassium chloride, sodium iodide, and sodium chloride. Among these, potassium iodide and potassium bromide are preferred. Only one type of halogen metal salt may be included, or two or more types may be included.

[0061] (ii) Examples of copper compounds include copper halides, copper salts (such as sulfates, acetates, propionates, benzoates, adipates, terephthalates, salicylates, nicotinates, and stearates), and copper chelate compounds (compounds of copper and ethylenediamine or ethylenediaminetetraacetic acid). Among these, copper iodide, cuprous bromide, cupric bromide, cuprous chloride, and copper acetate are preferred. Only one type of copper compound may be included, or two or more types may be included.

[0062] The mass ratio of (i) the halogen metal salt and (ii) the copper compound can be adjusted so that the molar ratio of halogen to copper is 0.1 / 1 to 200 / 1, preferably 0.5 / 1 to 100 / 1, and more preferably 2 / 1 to 40 / 1, from the viewpoint of easily improving the heat resistance of the molded body and the corrosiveness during production.

[0063] (iii) Examples of higher fatty acid metal salts include higher saturated fatty acid metal salts and higher unsaturated fatty acid metal salts.

[0064] The higher saturated fatty acid metal salt is preferably a metal salt of a saturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as an element in Groups 1, 2, or 3 of the Periodic Table, zinc, or aluminum. Such a higher saturated fatty acid metal salt is represented by the following formula (1). CH3(CH2) n COO(M1)...(1) (In formula (1), the metal element (M1) is an element in Groups 1, 2, or 3 of the Periodic Table of the Elements, zinc, or aluminum, and n can be 8 to 30.)

[0065] Examples of metal salts of higher saturated fatty acids include the lithium, sodium, magnesium, calcium, zinc and aluminum salts of capric acid, uracil acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid and lacteric acid.

[0066] The higher unsaturated fatty acid metal salt is preferably a metal salt of an unsaturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as an element in Groups 1, 2, or 3 of the Periodic Table, zinc, or aluminum.

[0067] Examples of metal salts of higher unsaturated fatty acids include lithium salts, sodium salts, magnesium salts, calcium salts, zinc salts and aluminum salts of undecylenic acid, oleic acid, elaidic acid, cetoleic acid, erucic acid, brassidic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, stearic acid, 2-hexadecenoic acid, 7-hexadecenoic acid, 9-hexadecenoic acid, gadoleic acid, gadoelaidic acid and 11-eicosenoic acid.

[0068] Examples of copper-based heat stabilizers include a mixture of 10% by mass of copper(I) iodide and 90% by mass of potassium iodide, and a mixture of 14.3% by mass of copper(I) iodide and 85.7% by mass of potassium iodide / calcium distearate (98:2 mass ratio).

[0069] The content of the copper-based heat stabilizer in the resin composition can be 0.01% by mass or more and 3% by mass or less, preferably 0.1% by mass or more and 3% by mass or less, more preferably 0.1% by mass or more and 0.5% by mass or less, based on the total mass of the resin composition. When the amount of the copper-based heat stabilizer is 0.01% by mass or more based on the total mass of the resin composition, the fluidity and heat aging resistance of the resin composition can be further improved. Also, when the amount is 3% by mass or less, the mechanical strength of the molded product is not easily impaired.

[0070] In addition, the content of copper contained in the copper-based heat resistance stabilizer in the resin composition is 0.001 parts by mass or more and 0.050 parts by mass or less, preferably 0.002 parts by mass or more and 0.040 parts by mass or less, more preferably 0.003 parts by mass or more and 0.030 parts by mass or less, and even more preferably 0.005 parts by mass or more and 0.025 parts by mass or less, when the total content of all polyamide resins contained in the polyamide resin composition is 100 parts by mass. When the content of copper contained in the copper-based heat resistance stabilizer is 0.001% by mass or more relative to 100 parts by mass of polyamide resin, the fluidity and heat aging resistance of the resin composition can be further improved. In addition, when it is 0.050% by mass or less, the mechanical strength of the molded body is not easily impaired.

[0071] 1-3.Glass fiber The polyamide fibers may include glass fibers.

[0072] It is known that a reinforcing material such as glass fiber is blended to improve the impact resistance and rigidity of a polyamide resin composition. The glass fiber may be treated with a sizing agent or a surface treatment agent for the purpose of improving dispersibility in a polyamide resin (Patent Document 4, etc.). However, according to new findings by the present inventors, when glass fiber treated with a sizing agent having an acidic group such as a carboxyl group, an acid anhydride group, or an ester group is added to a polyamide resin composition, the fluidity of the polyamide resin composition may decrease. The above-mentioned decrease in fluidity was also observed when glass fiber treated with a sizing agent or a surface treatment agent having another acidic group was added to a polyamide resin composition.

[0073] According to the findings of the present inventors, the decrease in the fluidity of the polyamide resin composition when glass fibers treated with a sizing agent or surface treatment agent having an acidic group are added to the molten polyamide resin composition is believed to occur due to the reaction of the acidic group of the sizing agent or surface treatment agent with the amino terminal of the polyamide resin. In other words, the reaction bonds the polyamide resin and the glass fibers via the sizing agent or surface treatment agent, increasing the apparent molecular weight of the polyamide resin. The increase in the apparent molecular weight is believed to decrease the fluidity of the polyamide resin composition. In contrast, the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane bends the molecular chain of the polyamide resin to cause moderate steric hindrance, inhibiting the reaction between the acidic group of the sizing agent or surface treatment agent and the amino terminal of the polyamide resin. This is believed to suppress the increase in the apparent molecular weight of the polyamide resin, thereby suppressing the decrease in the fluidity of the polyamide resin composition when a sizing agent or surface treatment agent having an acidic group is used.

[0074] The type of the glass fiber is not particularly limited as long as it is used to reinforce resin, and may be chopped strands or milled fibers having shorter fiber lengths, etc. The cross-sectional shape of the glass fiber may be circular or non-circular, such as elliptical or oval.

[0075] The average fiber length of the glass fiber may be, for example, from 1 μm to 20 mm, preferably from 5 μm to 10 mm, from the viewpoint of improving the moldability of the resin composition and the mechanical strength and heat resistance of the resulting molded article. The aspect ratio of the glass fiber may be, for example, from 5 to 2000, preferably from 30 to 600.

[0076] The average fiber length and average fiber diameter of the glass fibers can be measured by the following method. 1) The resin composition is dissolved in a hexafluoroisopropanol / chloroform solution (0.1 / 0.9% by volume), and then filtered to obtain a filtrate. 2) The filtrate obtained in 1) is dispersed in water, and the fiber length (Li) and fiber diameter (di) of each of 300 randomly selected fibers are measured using an optical microscope (magnification: 50x). The number of fibers with fiber length Li is designated as qi, and the weight average length (Lw) is calculated based on the following formula, which is the average fiber length of the glass fibers. Weight average length (Lw) = (Σqi × Li 2 ) / (Σqi×Li) Similarly, the number of fibers having a fiber diameter Di is defined as ri, and the weight average diameter (Dw) is calculated based on the following formula, and this is the average fiber diameter of the glass fibers. Weight average diameter (Dw)=(Σri×Di 2 ) / (Σri×Di)

[0077] The content of the glass fiber is not particularly limited, but can be, for example, 15% by mass or more and 70% by mass or less, preferably 15% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the polyamide resin composition.

[0078] In addition, the content of the above-mentioned glass fiber is not particularly limited, but is preferably 1 part by mass or more and 300 parts by mass or less, more preferably 10 parts by mass or more and 270 parts by mass or less, more preferably 20 parts by mass or more and 250 parts by mass or less, and even more preferably 30 parts by mass or more and 100 parts by mass or less, when the total content of all polyamide resins contained in the polyamide resin composition is 100 parts by mass.

[0079] The glass fibers include a surface treatment agent or a sizing agent.

[0080] The surface treatment agent or sizing agent may be a known surface treatment agent or sizing agent used for glass fibers to be blended in a polyamide resin composition. However, the surface treatment agent or sizing agent has an acidic group. Examples of the acidic group include a carboxy group, an acid anhydride group, an ester group, and a sulfonic acid group. Among these, a carboxy group, an acid anhydride group, and an ester group are preferred, and a carboxy group and an acid anhydride group are more preferred. The ester group may be a functional group derived from a carboxylic acid ester.

[0081] Examples of surface treatment agents having an acidic group include silane coupling agents containing an acid anhydride group such as 3-trimethoxysilylpropylsuccinic anhydride.

[0082] Examples of sizing agents having an acidic group include sizing agents containing a homopolymer or copolymer of an unsaturated carboxylic acid, or a copolymer of an unsaturated carboxylic acid or an anhydride thereof with an unsaturated monomer.

[0083] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, cinnamic acid, itaconic acid, fumaric acid, mesaconic acid, citraconic acid, and maleic acid. Examples of the anhydrides of the unsaturated carboxylic acids include maleic anhydride, itaconic anhydride, and dodecenylsuccinic anhydride. Of these, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred.

[0084] Examples of the unsaturated monomer include styrene, butadiene, acrylonitrile, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, methylstyrene, ethylene, propylene, butylene, isobutylene, and vinyl ether, etc. Among these, methyl acrylate and methyl methacrylate are preferred, and it is more preferred to include both methyl acrylate and methyl methacrylate.

[0085] When the sizing agent contains a copolymer of the unsaturated carboxylic acid or anhydride thereof and an unsaturated monomer, the ratio of the unsaturated carboxylic acid or anhydride thereof to the total mass of the copolymer is preferably 20% by mass or more and 60% by mass or less. When the ratio is 20% by mass or more, the effect of improving the mechanical strength of the polyamide resin composition is remarkable by increasing the chemical interaction with the polyamide resin by the acidic group (carboxy group). When the ratio is 60% by mass or less, the effect of improving the mechanical strength of the polyamide resin composition is remarkable by increasing the molecular weight (chain length) of the copolymer to enhance the physical interaction with the polyamide resin.

[0086] The above homopolymers or copolymers may be used in combination with other resins such as urethane resins and epoxy resins.

[0087] (Manufacturing method) The glass fibers containing the above-mentioned surface treatment agent or sizing agent can be obtained, for example, during the glass fiber manufacturing process, by applying (applying) the above-mentioned surface treatment agent or sizing agent to a fiber strand using a known method such as a roller-type applicator, and then drying and allowing to react.

[0088] The amount of the surface treatment agent or sizing agent attached is preferably 0.2 parts by mass or more and 3 parts by mass or less, more preferably 0.2 parts by mass or more and 2 parts by mass or less, and even more preferably 0.3 parts by mass or more and 2 parts by mass or less, based on 100 parts by mass of glass fiber. When the amount is 0.2 parts by mass or more, the bundling property of the glass fiber is further improved. Also, when the amount is 2 parts by mass or less, the thermal stability of the resin composition is further improved.

[0089] 1-4.Other ingredients The polyamide resin composition may contain other known components.

[0090] Examples of other components include reinforcing materials, crystal nucleating agents, lubricants, flame retardants, corrosion resistance improvers, drip prevention agents, ion scavengers, elastomers (rubbers), antistatic agents, mold release agents, antioxidants (phenols, amines, sulfurs, phosphorus compounds, etc.), heat stabilizers (lactone compounds, vitamin E compounds, hydroquinones, copper halides, iodine compounds, etc.), light stabilizers (benzotriazoles, triazines, benzophenones, benzoates, hindered amines, oxanilides, etc.), other polymers (polyolefins, olefin copolymers such as ethylene-propylene copolymers, ethylene-1-butene copolymers, olefin copolymers such as propylene-1-butene copolymers, polystyrene, polyamides, polycarbonates, polyacetals, polysulfones, polyphenylene oxides, fluororesins, silicone resins, and LCPs). Among these, the resin composition of the present disclosure preferably further contains a reinforcing material from the viewpoint of increasing the mechanical strength of the molded product.

[0091] The reinforcing material can impart high mechanical strength to the resin composition. Examples of the reinforcing material include fibrous reinforcing materials such as glass fiber, wollastonite, potassium titanate whiskers, calcium carbonate whiskers, aluminum borate whiskers, magnesium sulfate whiskers, zinc oxide whiskers, milled fiber, and cut fiber, as well as granular reinforcing materials. Of these, one type may be used alone, or two or more types may be used in combination. Among these, wollastonite, glass fiber, and potassium titanate whiskers are preferred, and wollastonite or glass fiber is more preferred, because they are easy to increase the mechanical strength of the molded body.

[0092] The average fiber length of the fibrous reinforcing material may be, for example, from 1 μm to 20 mm, preferably from 5 μm to 10 mm, from the viewpoint of moldability of the resin composition and mechanical strength and heat resistance of the resulting molded product. The aspect ratio of the fibrous reinforcing material may be, for example, from 5 to 2000, preferably from 30 to 600.

[0093] The average fiber length and average fiber diameter of the fibrous reinforcing material can be measured by the following method. 1) The resin composition is dissolved in a hexafluoroisopropanol / chloroform solution (0.1 / 0.9% by volume), and then filtered to obtain a filtrate. 2) Disperse the filtrate obtained in 1) in water, and measure the fiber length (Li) and fiber diameter (di) of each of 300 randomly selected fibers using an optical microscope (magnification: 50x). The number of fibers with fiber length Li is designated as qi, and the weight average length (Lw) is calculated based on the following formula, which is the average fiber length of the fibrous reinforcing material. Weight average length (Lw) = (Σqi × Li 2 ) / (Σqi×Li) Similarly, the number of fibers having a fiber diameter Di is defined as ri, and the weight average diameter (Dw) is calculated based on the following formula, and this is the average fiber diameter of the fibrous reinforcing material. Weight average diameter (Dw)=(Σri×Di 2 ) / (Σri×Di)

[0094] The content of the fibrous reinforcing material is not particularly limited, but can be, for example, from 15 mass % to 70 mass % relative to the total mass of the resin composition.

[0095] The crystal nucleating agent can increase the crystallinity of the molded body. Examples of the crystal nucleating agent include metal salt-based compounds including sodium 2,2-methylenebis(4,6-di-t-butylphenyl)phosphate, aluminum tris(pt-butylbenzoate), and stearates, sorbitol-based compounds including bis(p-methylbenzylidene)sorbitol and bis(4-ethylbenzylidene)sorbitol, and inorganic substances including talc, calcium carbonate, and hydrotalcite. Among these, talc is preferred from the viewpoint of further increasing the crystallinity of the molded body. These crystal nucleating agents may be used alone or in combination of two or more.

[0096] The content of the crystal nucleating agent is preferably 0.1 parts by mass or more and 5 parts by mass or less, and more preferably 0.1 parts by mass or more and 3 parts by mass or less, based on the total mass of the polyamide resin composition. When the content of the crystal nucleating agent is within the above range, the crystallinity of the molded product is easily increased sufficiently, and sufficient mechanical strength is easily obtained.

[0097] The lubricant enhances the injection flowability of the polyamide resin composition and improves the appearance of the resulting molded article. The lubricant can be a metal salt of a fatty acid, such as a metal salt of an oxycarboxylic acid or a metal salt of a higher fatty acid.

[0098] The oxycarboxylic acid constituting the oxycarboxylic acid metal salt may be an aliphatic oxycarboxylic acid or an aromatic oxycarboxylic acid. Examples of the aliphatic oxycarboxylic acid include aliphatic oxycarboxylic acids having 10 to 30 carbon atoms, such as α-hydroxymyristic acid, α-hydroxypalmitic acid, α-hydroxystearic acid, α-hydroxyeicosanoic acid, α-hydroxydocosanoic acid, α-hydroxytetraeicosanoic acid, α-hydroxyhexaeicosanoic acid, α-hydroxyoctaeicosanoic acid, α-hydroxytriacontanoic acid, β-hydroxymyristic acid, 10-hydroxydecanoic acid, 15-hydroxypentadecanoic acid, 16-hydroxyhexadecanoic acid, 12-hydroxystearic acid, and ricinoleic acid. Examples of the aromatic oxycarboxylic acid include salicylic acid, m-oxybenzoic acid, p-oxybenzoic acid, gallic acid, mandelic acid, and trovaic acid.

[0099] Examples of the metal constituting the metal oxycarboxylate include alkali metals such as lithium, and alkaline earth metals such as magnesium, calcium and barium.

[0100] Of these, the metal oxycarboxylate is preferably a metal salt of 12-hydroxystearic acid, and more preferably magnesium 12-hydroxystearate and calcium 12-hydroxystearate.

[0101] Examples of the higher fatty acid constituting the higher fatty acid metal salt include higher fatty acids having 15 to 30 carbon atoms, such as stearic acid, oleic acid, behenic acid, behenic acid, and montanic acid.

[0102] Examples of the metals constituting the above higher fatty acid metal salts include calcium, magnesium, barium, lithium, aluminum, zinc, sodium, and potassium.

[0103] Of these, the higher fatty acid metal salts are preferably calcium stearate, magnesium stearate, barium stearate, calcium behenate, sodium montanate, calcium montanate, and the like.

[0104] The content of the lubricant is preferably 0.01% by mass or more and 1.3% by mass or less based on the total mass of the polyamide resin composition. When the content of the lubricant is 0.01% by mass or more, the flowability during molding is likely to be improved, and the appearance of the obtained molded product is likely to be improved. When the content of the lubricant is 1.3% by mass or less, gas due to decomposition of the lubricant is unlikely to be generated during molding, and the appearance of the product is likely to be good.

[0105] 1-5. Manufacturing method The polyamide resin composition can be produced by a known resin kneading method, for example, by mixing the above-mentioned polyamide resin and, if necessary, other components with a Henschel mixer, V blender, ribbon blender, or tumbler blender, or by mixing and then melt-kneading the mixture with a single-screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer, followed by granulation or pulverization.

[0106] 2. Uses of resin composition The resin composition of the present disclosure can be molded by a known molding method such as compression molding, injection molding, or extrusion molding to be used as various polyamide molded articles.

[0107] The molded article of the resin composition of the present disclosure can be used for various applications.Examples of such applications include automotive exterior parts such as radiator grilles, rear spoilers, wheel covers, hubcaps, cowl vent grilles, air outlet louvers, air scoops, hood bulges, sunroofs, sunroof rails, fenders and back doors; automotive under-the-hood parts such as cylinder head covers, engine mounts, air intake manifolds, throttle bodies, air intake pipes, radiator tanks, radiator supports, water pump housings such as water pumps, water pump inlets, water pump outlets, water jacket spacers, thermostat housings such as thermostat housings, cooling fans, fan shrouds, oil pans, oil filter housings, oil filler caps, oil level gauges, oil pumps, timing belts, timing belt covers and engine covers; fuel caps, fuel filler tubes, automotive fuel tanks, fuel sender modules, fuel cut-off valves, quick connectors, canisters. automotive fuel system parts such as fuel delivery pipes and fuel filler necks; automotive drive system parts such as shift lever housings and propeller shafts; automotive chassis parts such as stabilizer bars, linkage rods, engine mount brackets; automotive functional parts such as window regulators, door locks, door handles, outside door mirror stays, wipers and their parts, accelerator pedals, pedal modules, joints, plastic screws, nuts, bushings, seal rings, bearings, bearing retainers, gears and actuators; automotive electronics parts such as wire harnesses and connectors, relay blocks, sensor housings, fuse parts, encapsulations, ignition coils and distributor caps; general-purpose equipment fuel system parts such as fuel tanks for general-purpose equipment (brush cutters, lawn mowers and chainsaws); electrical and electronic parts such as connectors and LED reflectors; building material parts, industrial equipment parts, as well as various housings or exterior parts such as small housings (including housings for personal computers and mobile phones) and exterior molded products.

[0108] In particular, the resin composition of the present disclosure is suitable for use in high temperature and high humidity environments, such as in-vehicle components, particularly in tubes through which antifreeze flows, because the mechanical strength of the resin composition is small even in high temperature and high humidity environments, and can be suitably used for thermostat housings, water pump housings, water jacket spacers, etc. Furthermore, it can be suitably used for in-vehicle components in which the environmental temperature is 100°C or higher, particularly turbo-related components, and high-voltage in-vehicle electrical components. In addition, the resin composition of the present disclosure can be suitably used for automotive electronics components, electrical and electronic components, industrial equipment components, and electrical equipment components such as housings or exterior parts for electrical equipment. EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples, which should not be construed as limiting the scope of the present disclosure.

[0110] In the following experiments, the melting point (Tm) and glass transition temperature (Tg) of the polyamide resin were measured by the following methods.

[0111] (Melting point (Tm), glass transition temperature (Tg)) The heat of fusion (ΔH), melting point (Tm) and glass transition temperature (Tg) of the polyamide resin were measured using a differential scanning calorimeter (DSC220C, manufactured by Seiko Instruments Inc.).

[0112] Specifically, about 5 mg of polyamide resin was sealed in a measuring aluminum pan and heated from room temperature to 350°C at 10°C / min. In order to completely melt the resin, it was held at 360°C for 3 minutes and then cooled to 30°C at 10°C / min. After leaving it at 30°C for 5 minutes, it was heated a second time to 360°C at 10°C / min. The temperature (°C) of the endothermic peak in this second heating was taken as the melting point (Tm) of the crystalline polyamide resin, and the transition point corresponding to the glass transition was taken as the glass transition temperature (Tg). The heat of fusion (ΔH) was calculated from the area of ​​the endothermic peak of crystallization during the first heating process in accordance with JIS K7122.

[0113] (Intrinsic viscosity [η]) The intrinsic viscosity [η] of the polyamide resin was determined by dissolving 0.5 g of the polyamide resin in 50 ml of a 96.5% sulfuric acid solution, measuring the flow time of the resulting solution at 25°C ± 0.05°C using an Ubbelohde viscometer, and calculating the intrinsic viscosity [η] = ηSP / (C(1 + 0.205ηSP)) based on the formula. [η]: Intrinsic viscosity (dl / g) ηSP: Specific viscosity C: Sample concentration (g / dl) t: Time required for sample solution to flow (seconds) t0: Number of seconds that blank sulfuric acid flows (seconds) ηSP=(t-t0) / t0

[0114] (Heat of fusion (ΔH)) The heat of fusion (ΔH) of the polyamide resin was calculated from the area of ​​the exothermic peak of crystallization during the first heating process in accordance with JIS K 7122 (2012).

[0115] 1. Synthesis / preparation of materials 1-1. Synthesis of polyamide resin (Synthesis Example 1) 259.5g (1561.7mmol) of terephthalic acid, 128.1g (1102.0mmol) of 1,6-diaminohexane, 67.2g (472.3mmol) of 1,3-bis(aminomethyl)cyclohexane, 0.37g of sodium hypophosphite monohydrate and 81.8g of distilled water were placed in an autoclave with a capacity of 1L and substituted with nitrogen. Stirring was started at 190°C, and the internal temperature was raised to 250°C over 3 hours. At this time, the internal pressure of the autoclave was raised to 3.0MPa. After continuing the reaction for 1 hour, the low-order condensation product was discharged into the atmosphere from a spray nozzle installed at the bottom of the autoclave and extracted. After that, the low-order condensation product was cooled to room temperature, pulverized to a particle size of 1.5mm or less with a pulverizer, and dried at 110°C for 24 hours.

[0116] Next, this low-order condensate was placed in a tray-type solid-phase polymerization apparatus, and after replacing with nitrogen, the temperature was raised to 215° C. over about 1 hour and 30 minutes, after which the reaction was continued for 1 hour and 30 minutes, and the temperature was lowered to room temperature.

[0117] The obtained prepolymer was then melt-polymerized in a twin-screw extruder with a screw diameter of 30 mm and L / D=36 at a barrel set temperature of 330° C., a screw rotation speed of 200 rpm, and a resin supply rate of 6 kg / h to obtain Polyamide Resin 1.

[0118] The resulting polyamide resin 1 had an intrinsic viscosity [η] of 0.9 dl / g, a melting point (Tm) of 323° C., a glass transition temperature (Tg) of 154° C., and a heat of fusion (ΔH) of 51 mJ / mg.

[0119] (Synthesis Example 2) Polyamide resin 2 was obtained in the same manner as in Synthesis Example 1, except that the amount of 1,6-diaminohexane and the amount of 1,3-bis(aminomethyl)cyclohexane placed in the autoclave were 118.9 g (1023.1 mmol), and 78.4 g (551.1 mmol), respectively. Polyamide resin 2 had an intrinsic viscosity [η] of 0.9 dl / g, a melting point (Tm) of 320°C, a glass transition temperature (Tg) of 156°C, and a heat of fusion (ΔH) of 48 mJ / mg.

[0120] (Synthesis Example 3) Polyamide resin 3 was obtained in the same manner as in Synthesis Example 1, except that the amount of 1,6-diaminohexane and the amount of 1,3-bis(aminomethyl)cyclohexane placed in the autoclave were 109.9 g (944.5 mmol), and 89.5 g (629.7 mmol), respectively. Polyamide resin 3 had an intrinsic viscosity [η] of 0.9 dl / g, a melting point (Tm) of 305°C, a glass transition temperature (Tg) of 166°C, and a heat of fusion (ΔH) of 35 mJ / mg.

[0121] (Synthesis Example 4) The amount of 1,6-hexanediamine placed in the autoclave was 280 g (2410 mmol), the amount of terephthalic acid was 277.4 g (1670 mmol), the amount of isophthalic acid was 119.6 g (720 mmol), 3.66 g (30 mmol) of benzoic acid was added, the amount of sodium hypophosphite monohydrate was 5.7 g, and the amount of distilled water was 545 g, but the same procedure as in Synthesis Example 1 was repeated to obtain polyamide resin 4. Polyamide resin 4 had an intrinsic viscosity of 1.0 dl / g, a melting point (Tm) of 330°C, a glass transition temperature (Tg) of 125°C, and a heat of fusion (ΔH) of 50 J / g.

[0122] 1-2.Copper-based heat stabilizer A mixture of 10% by mass of copper(I) iodide and 90% by mass of potassium iodide was used as a copper-based heat stabilizer.

[0123] 1-3. Lubricants Sodium montanate (manufactured by Clariant, LICOMONT NAV101 "LICOMONT" is a registered trademark of the company)

[0124] 1-4. Nucleating agents ·talc

[0125] 1-5. Reinforcement material Glass fiber (Owens Corning: FT-2A) (glass fiber surface modified by acid modification)

[0126] 2. Preparation of polyamide resin composition The above materials were mixed in a tumbler blender in the composition ratios (unit: parts by mass) shown in Tables 1 to 3, and melt-kneaded using a 30 mmφ vented twin-screw extruder at a cylinder temperature of 300 to 335°C. The kneaded mixture was then extruded in the form of strands and cooled in a water tank. The strands were then taken up and cut by a pelletizer to obtain a pelletized polyamide resin composition.

[0127] 3. Evaluation The obtained polyamide resin compositions were evaluated according to the following criteria.

[0128] 3-1. Tensile strength (at high temperatures) Each polyamide resin composition was injection molded under the following conditions to prepare a 3.2 mm thick ASTM-1 (dumbbell) test piece. Molding machine: SE50DU, manufactured by Sumitomo Heavy Industries, Ltd. Molding machine cylinder temperature: Polyamide resin melting point + 10℃ Mold temperature: Glass transition temperature of polyamide resin + 20℃ The prepared test piece was left for 24 hours in a nitrogen atmosphere at a temperature of 23° C. in accordance with ASTM D638. Then, a tensile test was performed in an atmosphere at a temperature of 140° C. in accordance with ASTM D638 to measure the tensile strength.

[0129] 3-2. Tensile strength retention rate before and after adding copper-based stabilizer The tensile strength at high temperature of the polyamide resin composition containing a copper-based stabilizer was compared with the tensile strength at high temperature of a polyamide resin composition containing the same amount of additives except that no copper-based stabilizer was contained, and the retention rate of flow length before and after the incorporation of glass fiber was calculated.

[0130] 3-3. Tensile strength (initial) The test piece was left for 24 hours in a nitrogen atmosphere at a temperature of 23° C. in accordance with ASTM D638. Then, a tensile test was performed in an atmosphere at a temperature of 23° C. and a relative humidity of 50% in accordance with ASTM D638 to measure the tensile strength.

[0131] 3-4. Tensile strength (after high temperature treatment) The test piece was left for 2000 hours at a temperature of 180° C. Thereafter, the test piece was allowed to cool to 23° C., and a tensile test was carried out in an atmosphere at a temperature of 23° C. and a relative humidity of 50% in accordance with ASTM D638 to measure the tensile strength.

[0132] 3-5. Tensile strength retention rate (after high temperature treatment) The initial tensile strength and the tensile strength after the high-temperature treatment were compared to calculate the ratio (retention rate) of the tensile strength after the high-temperature treatment to the initial tensile strength.

[0133] 3-6. Tensile strength (after high temperature and humidity treatment) The test piece was left for 48 hours at a temperature of 23° C. and a relative humidity of 50%. Thereafter, the test piece was allowed to cool to 23° C., and a tensile test was performed in an atmosphere at a temperature of 23° C. and a relative humidity of 50% in accordance with ASTM D638 to measure the tensile strength.

[0134] 3-7. Tensile strength retention rate (after high temperature and humidity treatment) The initial tensile strength and the tensile strength after the high-temperature and high-humidity treatment were compared to calculate the ratio (retention rate) of the tensile strength after the high-temperature treatment to the initial tensile strength.

[0135] 3-8.Flow length Each polyamide resin composition was injected into a barflow mold having a width of 10 mm and a thickness of 0.5 mm under the following conditions, and the flow length (mm) of the polyamide resin composition in the mold was measured. Note that a longer flow length indicates better injection flowability. Molding machine: Toshiba Machine Co., Ltd., EC75N-2A Injection pressure setting: 2000kg / cm 2 Molding machine cylinder temperature: 335℃ Mold temperature: 160℃

[0136] 3-9. Maintenance rate of flow length before and after blending with glass fiber The flow length of the polyamide resin composition containing a copper-based stabilizer and glass fiber, or the polyamide resin composition containing glass fiber, was compared with the flow length of a polyamide resin composition containing the same amount of additives except that no glass fiber was contained, and the retention rate of the flow length before and after the incorporation of glass fiber was calculated.

[0137] The composition, tensile strength (at high temperature), retention rate of flow length, tensile strength (initial), tensile strength (after high temperature treatment) and retention rate of tensile strength of the prepared polyamide resin compositions are shown in Tables 1 to 3. In Tables 1 to 3, the unit of copper / 100 parts by mass of polyamide resin in the copper-based stabilizer is parts by mass.

[0138] [Table 1]

[0139] [Table 2]

[0140] [Table 3]

[0141] As is clear from Tables 1 to 3, the polyamide resin having the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane can suppress the decrease in tensile strength at high temperatures caused by the addition of a copper-based heat stabilizer. Also, the polyamide resin having the component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane can suppress the decrease in mechanical strength in high temperature and high humidity environments.

[0142] As is clear from Tables 1 to 3, polyamide resins having component units (b2) derived from 1,3-bis(aminomethyl)cyclohexane can suppress the decrease in fluidity caused by the incorporation of glass fibers containing a surface treatment agent or a sizing agent having an acidic group.

[0143] This application claims priority to Japanese Application No. 2021-044984, filed on March 18, 2021, and the contents of the claims and specification of that application are incorporated by reference into this application. [Industrial Applicability]

[0144] According to the polyamide resin composition of the present disclosure, it is possible to improve mechanical strength by adding a copper-based heat stabilizer while suppressing a decrease in fluidity. Therefore, it is expected that the present disclosure will broaden the applicability of polyamide resins to various applications and contribute to the further popularization of polyamide resins.

Claims

1. A polyamide resin, Contains copper-based heat stabilizer, The polyamide resin is A polyamide resin comprising a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine, The dicarboxylic acid-derived component unit (a) includes an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid-derived component unit, The diamine-derived component unit (b) is a component unit (b1) derived from an alkylene diamine having from 4 to 18 carbon atoms, the component unit (b1) being from more than 50 mol % to 90 mol % of the total number of moles of the component unit (b) derived from the diamine; a component unit (b2) derived from 1,3-bis(aminomethyl)cyclohexane, which is 10 mol % or more and less than 50 mol % of the total number of moles of the component unit (b) derived from the diamine; Including, The copper content in the copper-based stabilizer is 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin contained in the polyamide resin composition. Polyamide resin composition.

2. 2. The polyamide resin composition according to claim 1, further comprising glass fibers containing a surface treatment agent having an acidic group or a sizing agent having an acidic group in an amount of 1 part by mass or more and 300 parts by mass or less per 100 parts by mass of the polyamide resin contained in the polyamide resin composition.

3. The polyamide resin composition according to claim 2 , wherein the acidic group is a carboxy group, an acid anhydride group, or an ester group.

4. The polyamide resin composition according to any one of claims 1 to 3, wherein the polyamide resin contains 15 mol% or more and less than 45 mol% of component units (b2) derived from 1,3-bis(aminomethyl)cyclohexane, based on the total number of moles of the component units (b) derived from the diamine.

5. The component unit (b1) derived from an alkylenediamine having 4 to 18 carbon atoms includes a component unit derived from a linear alkylenediamine or a branched alkylenediamine. The polyamide resin composition according to any one of claims 1 to 4.

6. The linear or branched alkylenediamine is a diamine selected from the group consisting of 1,4-diaminobutane, 1,6-diaminohexane, 1,9-nonanediamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine and 2-methyl-1,8-octanediamine; The polyamide resin composition according to claim 5.

7. The aromatic dicarboxylic acid or alicyclic dicarboxylic acid is terephthalic acid, naphthalenedicarboxylic acid or cyclohexanedicarboxylic acid; The polyamide resin composition according to any one of claims 1 to 6.

8. The polyamide resin composition according to any one of claims 1 to 7, which is a resin composition for an on-vehicle member.

9. The polyamide resin composition according to any one of claims 1 to 8, Polyamide molding.

10. In-vehicle components: The polyamide molding according to claim 9.

Citation Information

Patent Citations

  • JP1974055796A

  • Polyamide resin composition

    JP1994032979A

  • Glass fiber sizing agent, glass fiber, and glass fiber-reinforced polyamide resin

    JP2014231452A

  • Copolyamides, molding materials comprising the same, and molded articles produced therefrom

    JP2017075303A

  • Polyamide molding material and molded article thereof

    JP2018178117A